2015
DOI: 10.1002/jor.22980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lubricant and autologous bone marrow stromal cell augmentation on immobilized flexor tendon repairs

Abstract: The purpose of the study was to test a novel treatment that carbodiimide-derivatized-hyaluronic acid-lubricin (cd-HA-lubricin) combined cell-based therapy in an immobilized flexor tendon repair in a canine model. Seventy-eight flexor tendons from 39 dogs were transected. One tendon was treated with cd-HA-lubricin plus an interpositional graft of 8 × 105 BMSCs and GDF-5. The other tendon was repaired without treatment. After 21 day of immobilization, 19 dogs were sacrificed; the remaining 20 dogs underwent a 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…MSCs are multipotent stem cells with significant potential in the field of regenerative medicine. Numbers of previous studies have demonstrated beneficial effects of BMSCs implantation in improving tendon healing after injury . Pacini et al used suspension of undifferentiated BMSCs for equine superficial digital flexor tendon repair and reported improved outcome .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are multipotent stem cells with significant potential in the field of regenerative medicine. Numbers of previous studies have demonstrated beneficial effects of BMSCs implantation in improving tendon healing after injury . Pacini et al used suspension of undifferentiated BMSCs for equine superficial digital flexor tendon repair and reported improved outcome .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been successfully identified and isolated from a variety of tissues including adipose tissue, umbilical cord, bone marrow, amniotic fluid, skeletal muscle, and cartilage, among which bone marrow‐derived MSCs (BMSCs) is most commonly used for tissue regeneration and cell therapy because of their easy accessibility and expandability . Recently, regenerative approaches incorporating BMSCs delivery have been explored using in vivo or ex vivo model, with promising evidences showing promoted flexor tendon repair and healing . Concomitantly, BMSCs have been isolated from several experimental animals for the growing interest and needs of utilizing cell‐based therapies .…”
mentioning
confidence: 99%
“…10,16 More than 80% of the dry weight of a tendon is composed of COL1 and COL3. 17 Production of COL1 and COL3 indicates the cell tenogenic phenotype and activity. 10 Our study showed that mechanical stimulation with seeded BMSCs upregulated COL1 expression more than 30-fold and COL3 expression more than ten-fold compared with BMSC treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This safe, targeted, sustained delivery approach represents a significant improvement compared to previous growth factor delivery strategies for tendon repair. 11,15,17 …”
Section: Discussionmentioning
confidence: 99%